Healthy Relationships: The Adoption, Adaptation, and Implementation of a DEBI Within Two Clinical Settings. Issue 3 (May 2015) - Precht, Allison M.; Ryerson Espino, Susan; Villela Perez, Veronica; Ingram, Mercedes Vaughn; Amodei, Nancy; Miller, Amanda; Gonzalez, Marisol
The use of evidence-based interventions is increasingly expected within public health settings. However, there continues to be an evidence gap between what works in the literature and in practice. The current multiple case study focused on the adoption, adaptation, capacity building, implementation, and evaluation of healthy relationships (HR) in two demonstration project sites. Our lens for reflection and writing has been highly practical, with an aim of sharing experiences with others interested in adopting HR or another Diffusion of Effective Behavioral Interventions in clinical settings with resource challenges. Although both sites recognized the powerful influence HR had on participants and staff, they reported that HR is resource-intensive regarding training, implementation, and evaluation, limiting the possibility of sustaining the intervention.